Boron ameliorates arsenic‐induced DNA damage, proinflammatory cytokine gene expressions, oxidant/antioxidant status, and biochemical parameters in rats. Issue 2 (28th October 2018) - Ince, Sinan; Kucukkurt, Ismail; Acaroz, Ulas; Arslan‐Acaroz, Damla; Varol, Nuray
Abstract: Arsenic, an element found in nature, causes hazardous effects on living organisms. Meanwhile, natural compounds exhibit protective effects against hazardous substances. This study evaluated the effects of boron against arsenic‐induced genotoxicity and altered biochemical parameters in rats. Thirty‐five male Wistar albino rats were equally divided into five groups, and the experimental period lasted 30 days. One group was used as the control, and another group was treated with 100 mg/L arsenic in drinking water. The other groups were orally treated with 5, 10, and 20 mg/kg boron plus arsenic (100 mg/L via drinking water). Arsenic caused changes in biochemical parameters, total oxidant/antioxidant status, and DNA damage in mononuclear leukocytes. Moreover, it increased IFN‐γ, IL‐1β, TNF‐α, and NFκB mRNA expression levels in rat tissue. However, boron treatment improved arsenic‐induced alterations in biochemical parameters and increases in DNA damage and proinflammatory cytokine gene expressions.